Effect of Geography and Captivity on Scat Bacterial Communities in the Imperiled Channel Island Fox - Adams, Nicole E.; Becker, Madeleine A.; Edmands, Suzanne (Frontiers in Microbiology, 2021)
With developing understanding that host-associated microbiota play significant roles in individual health and fitness, taking an interdisciplinary approach combining microbiome research with conservation science is increasingly favored. Here we establish the scat microbiome of the imperiled Channel Island fox (Urocyon littoralis) and examine the effects of geography and captivity on the variation in bacterial communities. Using high throughput 16S rRNA gene amplicon sequencing, we discovered distinct bacterial communities in each island fox subspecies. Weight, timing of the sample collection, and sex contributed to the geographic patterns. We uncovered significant taxonomic differences and an overall decrease in bacterial diversity in captive versus wild foxes. Understanding the drivers of microbial variation in this system provides a valuable lens through which to evaluate the health and conservation of these genetically depauperate foxes. The island-specific bacterial community baselines established in this study can make monitoring island fox health easier and understanding the implications of inter-island translocation clearer. The decrease in bacterial diversity within captive foxes could lead to losses in the functional services normally provided by commensal microbes and suggests that zoos and captive breeding programs would benefit from maintaining microbial diversity.